2021
DOI: 10.1186/s12967-021-02738-0
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor immunogenomic signatures improve a prognostic model of melanoma survival

Abstract: Background Tumor mutation burden (TMB) has been associated with melanoma immunotherapy (IT) outcomes, including survival. We explored whether combining TMB with immunogenomic signatures recently identified by The Cancer Genome Atlas (TCGA) can refine melanoma prognostic models of overall survival (OS) in patients not treated by IT. Methods Cox proportional-hazards (Cox PH) analysis was performed on 278 metastatic melanomas from TCGA not treated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Additionally, low sample size may have contributed to this finding. As an example, utilizing the objective response rate of 45% for nivolumab monotherapy and 58% for ipilimumabnivolumab therapies reported in a previous landmark clinical trial (20), a sample size of 462 patients would be required to detect differences at a type II error rate of <0.20. The sample size of this study (n=198) was comparatively modest, possibly accounting for why our results deviate from those reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, low sample size may have contributed to this finding. As an example, utilizing the objective response rate of 45% for nivolumab monotherapy and 58% for ipilimumabnivolumab therapies reported in a previous landmark clinical trial (20), a sample size of 462 patients would be required to detect differences at a type II error rate of <0.20. The sample size of this study (n=198) was comparatively modest, possibly accounting for why our results deviate from those reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true if reducing tumour burden is necessary to prolong life and palliate related symptoms. Many different markers, including those focusing on tumour characteristics and other clinical parameters, have been proposed as putative candidate factors (19)(20)(21)(22)(23). However, attempts to discriminate patient populations using these markers are infrequent, with a lack of studies focused on patients with advanced melanoma treated with first-line ICI therapies in a realworld setting (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chen et al constructed a nine-iron-death-associated gene prognostic model, which showed great performance in terms of predicting melanoma prognosis [ 29 ]. Another study constructed an immunogenomic signature prognostic model based on gene expression data derived from TCGA to predict overall survival in melanoma [ 30 ]. A recent study used a six-gene model-based prognostic approach to treat melanoma patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%